Estudo da hidrólise do óleo de soja catalizada pela enzima lipozyme TL IM - Focking, Andriele Magarinos (2017)
The utilization of biodiesel as a substitute for diesel oil is one of the alternatives that aims to minimize the utilization of non-renewable fuels (petroleum) in the world energy matrix. Worldwide, biodiesel production occurs through the transesterification process. In Brazil, the most commonly used raw material for this purpose is soybean oil. A new way that has been promising for the biodiesel production is the Hidroesterification process. With that, the present work a imed to evaluate the soy oil enzymatic hydrolysis, using the comercial enzyme Lipozyme TL IM as the catalyst of the reaction. Was performed hydrolysis test of soy oil in closed and batch system, based on two experimental plannings (Placket-Burmann ad DCCR), to evaluate the effects of the variables involved in the process(pH; temperature; molar fraction water/oil; stirrings peed of the batch reactor and mass fraction enzyme/substrate). Since that, was perfomed kinetic studies with different conditions of molar fraction water/oil and different dosages of catalyst, as well as the utilization of a tip ultrasonic and a chemical agent to evaluateit’s effects on the kinetic of the reaction. To describe the kinetic of enzymatic hydrolysis of soy oil, was used a mathematical model based on the Michaelis-Menten kinetic. The results of experimental planningsindicatedthattheaciditylevelswerefavoredwhenthetemperatureof 52,2ºC, pH 6.1, stirring speed 150 rpm and molar fraction water/oil 37,7:1, getting 82,4% in the value of acidity level. The kinetic studies showed that the utilization of the probe ultrasonic did not accelerated the velocity of the enzymatic hydrolysis reaction. The kinetic involving the utilization of the chemical agent suffered a high decrease in the velocity of reaction, showing that this would be a inhibitor of enzymatic activity of Lipozyme TL IM. By the mathematical model, was verified that the model described well the experimental datas, as well made able the visualization of others components concentration (triacylglycerols, diacylglycerols, monoacylglycerols, glycerol, free fatty acids and water). It is believed that the values of the constants of the reaction velocity obtained in the model has more physical meaning and could be used to conducting the simulations in anothers conditions.